Peptidylarginine deiminase inhibition impairs Toll‐like receptor agonist‐induced functional maturation of dendritic cells, resulting in the loss of T cell–proliferative capacity: a partial mechanism with therapeutic potential in inflammatory settings. Issue 2 (24th November 2014) - Jang, Byungki; Kim, Ho Won; Kim, Jong‐Seok; Kim, Woo Sik; Lee, Bo Ryeong; Kim, Sojeong; Kim, Hongmin; Han, Seung Jung; Ha, Sang‐Jun; Shin, Sung Jae
Abstract : Peptidylarginine deiminase role in inflammatory settings viaalteration of the functional maturation of DCs. Abstract : Cl‐amidine, which is a small‐molecule inhibitor of PAD, has therapeutic potential for inflammation‐mediated diseases. However, little is known regarding the manner by which PAD inhibition by Cl‐amidine regulates inflammatory conditions. Here, we investigated the effects of PAD inhibition by Cl‐amidine on the functioning of DCs, which are pivotal immune cells that mediate inflammatory diseases. When DC maturation was induced by TLR agonists, reduced cytokine levels (IL‐6, IL‐1 β, and IL‐12p70) were observed in Cl‐amidine‐treated DCs. Cl‐amidine‐treated, LPS‐activated DCs exhibited alterations in their mature and functional statuses with up‐regulated antigen uptake, down‐regulated CD80, and MHC molecules. In addition, Cl‐amidine‐treated DCs dysregulated peptide‐MHC class formations. Interestingly, the decreased cytokines were independent of MAPK/NF‐ κ B signaling pathways and transcription levels, indicating that PAD inhibition by Cl‐amidine may be involved in post‐transcriptional steps of cytokine production. Transmission electron microscopy revealed morphotypical changes with reduced dendrites in the Cl‐amidine‐treated DCs, along with altered cellular compartments, including fragmented ERs and the formation of foamy vesicles. Furthermore, in vitro and in vivo Cl‐amidine treatments impaired the proliferation of nai¨ve CD4 + and CD8 + T cells. Overall, our findings suggest that Cl‐amidine has therapeutic potential for treating inflammation‐mediated diseases.